Enriquecimientos ambientales y su efecto en la manifestación de comportamientos estereotipados en Osos de anteojos (tremarctos ornatus) del eco zoológico San Martín en Baños de Agua Santa – Tungurahua. - Caiza Sevilla, Sofia Isabel (2022)
The purpose of this research project was to evaluate the application of environmental enrichments (E. E.) in two Andean bears (Tremarctos ornatus) of the San Martín Eco Zoo in Baños de Agua Santa – Tungurahua to verify its effect on the manifestation of natural and stereotyped behaviours. For this study, a quasi-experimental research design was applied, taking into consideration the sample limited to two Andean bears; therefore, a focal sampling method was used to record the behaviour of the ursids. These were evaluated from December 2021 to January 2022, accounting for a total of 19 activities, 15 daily activities and 4 stereotyped. Subsequently, ethograms were developed and applied for five days to determine the frequency and duration that individuals dedicated to these activities. The results of the evaluation were submitted to a diagnostic phase in which the environmental enrichments were selected through the SPIDER method. In this way, a program of four environmental enrichments of a structural, nutritional, and sensory type was proposed. The application period for each E. E. was three days, and the application of ethograms was carried out before and after environmental enrichment. Finally, the results indicated that three of the four E. E. applied are favourable; these were obtained through a comparison of the behaviours by means of a t-test for means of two paired samples from before and after the E. E. with a significance value of (p<0.05) in most daily and stereotyped activities.